A photoactive Ir–Pd bimetallic cage with high singlet oxygen yield for efficient one/two-photon activated photodynamic therapy. (7th March 2022) - Liu, Yuan-Yuan; Yu, Hui-Juan; Wang, Ya-Ping; Li, Chao-Jie; Wang, Xiao-Fei; Ye, Cai-Guo; Yao, Hong-Liang; Pan, Mei; Su, Cheng-Yong
Abstract : Photodynamic therapy (PDT) has been extensively studied as a noninvasive treatment option; however, the current PDT agents are often restricted with poor solubility, difficult accumulation in tumor sites, low singlet oxygen yield and low penetration depth. Abstract : Photodynamic therapy (PDT) has been extensively studied as a noninvasive treatment option; however, the current PDT agents are often restricted with poor solubility, difficult accumulation in tumor sites, low singlet oxygen yield and low penetration depth. Herein we develop a one-/two-photon excitation [Pd4 Ir8 ] 16+ supramolecular cage (MOC-53) comprising multiple Ir(iii ) metalloligands, which can be quickly taken up by cancer cells to locate in the mitochondria with an ultra-high singlet oxygen generation efficiency (0.84). In particular, MOC-53 also exhibits singlet oxygen generation capability under two-photon excitation to enhance the depth of penetration and reduce photo-damage. JC-1 assays, Annexin V-FITC/PI assays and the activity of caspase-3/7 analyses show that MOC-53 can activate apoptosis efficiently. The tumor volume growth of mice after the intra-tumoral injection of MOC-53 is obviously restrained under the two-photon irradiation, showing a potential opportunity for photodynamic cancer treatment.